Ahli Waris dan Cara Pembagian Waris Berdasarkan Undang-Undang - Agus Indra Cahyadi; Umarullah Missasi; Rosdianto; Muannif Ridwan; Agung Setiabudi (Universitas Islam Indragiri, 2024)
The main objective of this study is to explain about heirs and their distribution based on the Law. The method used in this study uses the normative juridical method, namely referring to the provisions of positive legal regulations in Indonesia, especially laws and regulations on inheritance law. Talking about inheritance, it is inseparable from the death of a person. Inheritance law is the law that regulates the transfer of assets left by a deceased person and the consequences for the heirs or their heirs. Inheritance according to Islamic Law regulates the principles of inheritance, conditions and pillars of inheritance, heirs, and regulations regarding the amount of inheritance received by the heirs. Sourced from the Qur'an, hadith, ijma' and ijtihad, inheritance according to Islamic Law then developed in the lives of Indonesian society until the enactment of the Compilation of Islamic Law (KHI) as an application of Islamic law in Indonesia, including regarding inheritance. In Islamic teachings, the issue of inheritance plays a very important role. In some Muslim communities, conflicts often arise between fellow heirs regarding the distribution of inheritance. Therefore, it is very important for Muslim communities to know the issue of inheritance in Islam.